Identificação de elementos logísticos de desempenho relacionados aos conflitos no canal de distribuição de cerveja - Cavalcante, Eduardo Borges (2012)
The distribution channels of a sector are composed of a set of interdependent organizations involved in the process of making available a product or service for use or consumption. When considering the frequent changes and storms from the market, it is important that the company have the ability to develop and administer, with success, their relationships with other members of the channel of distribution, in order to minimize conflicts that may occur in this channel. These companies, however, have difficulty in monitoring and evaluating the performance and impact of members ' perception of that channel in relation to logistical elements in relationship issue (conflict) in the channel. Thus, the objective of this paper is to measure the perception of distribution channel members in respect of logistics elements and if these may or may not lead to conflicts. The search is characterized as descriptive. For the survey of applied survey data, by means of a questionnaire on the sample comprised of 195 customers served by resale, random not defined, in which by means of questions using the Likert scale, which ranged from 1 to 5, their perceptions were assessed in relation to the elements of logistics operational performance and availability, quality, considering the service performed by the Distributor X. data have been analyzed quantitatively, having initially applied scale test to measure the reliability of logistics elements. The following was employed multivariate analysis to verify the significance of chance shown and, since the data is displayed on a non-normal, was applied the test not parametric Mann-Whitney with views to test the hypotheses. Even without normality of the sample was done a test average analysis (ANOVA), which showed results close to test parametric not found. It was noted that the Operating Performance elements and two of its sub-elements (order cycle speed and fault recovery) showed statistically significant differences between the perception of respondents with the channel conflict and the perception of these items in respondents without channel conflict, indicating that these variables, in the sample investigated, may have a relationship with what is called a vertical conflict in distribution channels.